Fenomena Ore Ore Sagi sebagai Bentuk Penipuan terhadap Kerentanan Lansia dalam Masyarakat Hyper-Aging Jepang - Putri Elsy (Universitas Airlangga, 2026)
The “Ore Ore Sagi” phenomenon is a form of telephone fraud that often targets older adults in Japan. The term “ore, ore” literally means “me, me”, an informal expression used by young men. In this scam, perpetrators pretend to be the children or grandchildren of older adults who are facing an urgent situation, thereby persuading victims to provide immediate financial assistance. Meanwhile, “sagi” means “fraud”. This study aims to analyze the “Ore Ore Sagi” phenomenon as a form of fraud targeting older adults in Japan's rapidly aging society. “Ore-Ore Sagi” has existed since 2009. The rapid increase in the population of adults aged 65 and above has made older adults primary targets of this type of fraud. This study employs a literature review method by examining documented cases and police reports related to “Ore Ore Sagi”. The findings indicate that older adults are vulnerable to this form of fraud. “Ore Ore Sagi” is associated not only with criminal activity, but also with the vulnerability of older adults, including social isolation, limited digital literacy, and excessive trust in individuals claiming to be their children or grandchildren. These factors make victims reluctant to ask questions to verify the caller's identity for fear of appearing unfamiliar with their own family members. In addition to causing financial losses amounting to billions of yen each year, “Ore Ore” scams also inflict psychological trauma, further exacerbating the vulnerability of older adults. Therefore, “Ore, Ore” scams have become a significant social issue amid demographic change and the cultural dynamics of Japan's hyper-aging society.